Kemampuan Translasi Representasi Siswa pada Materi Aljabar Berdasarkan Tingkat Kemampuan Matematis Kelas VIII MTs PSM Tanen - Ula, Vivi Ni’matul; Hadi, Syaiful (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2023)
Representation has various forms in conveying ideas, such as symbols, verbal, graphs, and  tables.  In  changing  from  the  source  representation  to  the  requested  target representation,  students  must  have  representational  translation  skills,  especially  in algebra. Representational translation ability is important for students because it can prevent misunderstanding in solving math problems and help understanding algebra material.  This  study  aims  to  describe  the  representational  translation  ability  of students with different levels of mathematical ability in the algebra material of class VIII MTs PSM Tanen. The results showed that students with high mathematical ability were able to fulfill most of the indicators for representational translation from verbal form to symbolic form (V-S), but not fully on the translation from symbolic to verbal form (S-V). Students with moderate mathematical ability can fulfill most of the V-S indicators,  but  have  limitations  in  S-V.  Meanwhile,  students  with  low  mathematics ability were not able to fulfill the V-S or S-V indicators. In conclusion, representational translation ability varies between students with high, medium, and low mathematics ability.  Students  need  to  be  helped  to  improve  this  translational  ability  in  order  to understand and solve math problems better, especially in algebra material.